Multidimensional and monetary poverty in South Sulawesi Province - Rahman, Zainuddin; Mawali, Asep Yahya; Purnama, Hukma Ratu (Indonesian Journal of Multidisciplinary Science, 2023)
The objective of this study is calculate and analyze multidimensional poverty occurred in South Sulawesi in 2011 and 2015, and looking at the comparison calculation results multidimensional poverty and monetary (based on expenditure per capita per month) that occurred in South Sulawesi in 2011 and 2015. This study uses secondary data sources from the National Socio-Economic Survey (Survei Sosial Ekonomi Nasional-Susenas) in 2011 and 2015 which have been implemented by Statistics South Sulawesi province to the identification and aggregation of multidimensional poverty. Dimensions, indicators/variables, cuttoff and weights used is based upon the Global Multidimensional Poverty Index with some adjustments at the indicators used. While monetary poverty data source is the official poverty statistic released. The results of this study indicate that (1) multidimensional poverty in South Sulawesi Province is a rural phenomenon as indicated by the three indicators of multidimensional poverty is higher than urban; (2) The dimensions of health is the largest contributor of multidimensional poverty in South Sulawesi; (3) Monetary Poverty create a different description from non-monetary dimensions, the entire district/city in South Sulawesi have the results of multidimensional poverty which higher than the monetary poverty; (4) The decline in the percentage of poor monetary occurred during the years 2011-2015 in the province was followed by a decrease in the percentage of poor multidimensional with a faster decline; (5) Spatially recorded 22 districts/cities in South Sulawesi are in the poor category multidimensional high and very high in 2011, in 2015 only 14 districts were still at that level.